An Analysis of Clothing Perception through Fashion Image - Hyekyun Kim; Ella Kidd (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is an exploratory study that examines the selective process of unique fashion through photography. While society has the ability to influence thinking, we investigated the preference for unique attire among undergraduates of AsianAmerican (Bai-Culture) universities. Participants in this study (N=28) were targeted at two different groups of Koreans and Kazakh nationals enrolled in private universities, and among the methods of analysis, nonparametric methods, or Mann-Whitney U, were analyzed to analyze the preference of clothing of business administration majors at W University. The results showed that in choosing "unique" attire, open thinking and more individualistic and unaffected in the cataclysmic aspect. Based on data results, fashion photography is an essential and influential indicator in choosing styles between gender and culture.